PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV MATERI AKU DAN KEBUTUHANKU - Neti N. Mantolas; Wahyu Susiloningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem-based learning model is an educational approach model that emphasizes the active role of students in the learning process by providing real problems to be solved. This study aims to determine the effect of the problem-based learning model on student learning outcomes in the fourth grade science subject on the material Me and My Needs. The study used a quantitative approach with a quasi-experimental design. The subjects of the study were 54 fourth grade students of SDN Menanggal 601 Surabaya. According to the findings of the research that has been carried out, the T-test indicated that the posttest score for the experimental class reached 78.51, while the control class was only 66.22. In addition, the hypothesis analysis using the independent T-test obtained a significant value of 0.000. Keywords: Problem Based Learning Model, Learning Outcomes, IPAS